Management of Posterior Glottal Insufficiency With Use of a Buccal Graft. (February 2017) - Helman, Samuel N.; Karle, William; Pitman, Michael J.
Objective: Posterior glottal insufficiency manifests as a rough, breathy voice with poor vocal projection, air hunger, and decreased phonatory efficiency. There are limited medical and surgical therapies. This study reports the use of insetting a buccal mucosa graft into the posterior interarytenoid space to close the posterior glottic gap for phonatory rehabilitation. Methods: Our study is a retrospective case series of 2 female patients undergoing buccal mucosa graft inset to repair acquired posterior glottic insufficiency as a result of prolonged intubation and laryngeal tuberculosis infection. Patients selected for this procedure had posterior glottal insufficiency due to erosion of posterior glottal tissue. They also had dysphonia refractory to voice therapy and injection augmentation. Conclusions: Interarytenoid buccal graft for posterior glottal insufficiency is effective with excellent vocal rehabilitation and minimal donor site morbidity.